ACTR-28. A CALL FOR INCREASED ROLE OF NEUROSURGEONS IN SURGICAL TRIALS FOR NON-GLIOMATOUS PRIMARY CNS TUMORS: A SYSTEMATIC REVIEW OF THE CLINICALTRIALS.GOV DATABASE. (11th November 2019) - Mansouri, Alireza; Beyn, Michelle; Chow, Clement; Pancholi, Aditya; Boutet, Alexandre; Elias, Gavin; Germann, Jurgen; Zadeh, Gelareh
Abstract: BACKGROUND: Surgery continues to be part of the mainstay of therapy for most primary CNS tumors. However, neurosurgical innovations advancing treatment options have stagnated. An understanding of past and current investigational trends is necessary to catalyze innovation in surgical trials. OBJECTIVE: To evaluate the landscape of surgical clinical trials for non-diffusely infiltrating primary CNS tumors. METHODS: ClinicalTrials.gov was searched on May 14 th, 2019 for surgical/procedural trials based on non-diffusely infiltrating primary CNS tumors, with a focus on meningiomas, ependymomas, medulloblastomas, pituitary adenomas, vestibular scwhannomas, and chordomas. Key trial design parameters were extracted. Purely surgical interventions were classified as "technical" while fluorescence-guided and other intraoperative imaging modalities were classified as image-guided surgery. Any invasive mode of drug delivery (e.g. intra-arterial or intra-ventricular, local chemotherapy wafers, and oncolytic virus injection) was considered. RESULTS: Among 944 total trial records (257 medulloblastomas, 254 ependymomas, 179 meningiomas, 156 pituitary adenomas, 56 vestibular schwannomas, and 48 chordomas) only 54 (5.7%) were procedural in nature. Ependymomas had the highest absolute number (18/254, 7%) while vestibular schwannomas had the highest percentage (6/56, 10.7%) of surgical trials. The majority of records were not randomized (41/54, 75.9%), not industry-funded (45/54, 83.3%), and were early Phase (30/54, 55.6%); there were only three Phase III trials. The relative number of new surgical trial registrations has not changed significantly over time (1990s: 5, 2000s: 19, and 2010s: 30). Approaches integrated with other disciplines, such as image-guided surgery (16/54, 29.6%) and local drug delivery (16/24, 29.6%), were among the leading categories of trials. CONCLUSIONS: Despite the clinical role of surgery in management of non-diffusely infiltrating primary CNS tumors, a paucity of innovative surgical trials has been put forth. Multi-disciplinary approaches appear to be necessary for pushing the therapeutic envelope for individuals affected by these tumors, with imaging and drug development at the forefront.